Pemasaran Retorika Politik dalam Iklan Baliho Tokoh Politik Indonesia - Adi Pamungkas (Kalijaga Journal of Communication, 2022)
This study subjects to understand how the politicians build identity through the marketing of their political rhetoric in billboard advertisements. The research uses qualitative methods with a substance theory approach to the formation of political identity, especially in the context of political marketing and Aristotle's rhetoric in the form of aspects 1) ethos; morally proper attitude, 2) logos; evidence that can support the argument and 3) pathos; speech that evokes feelings in the audience. The findings explain that the political identity built by various rhetoric aspect. Between the politicians also build different identity according to the consideration of internal aspects of the politicians and external aspects that exist in public. Through the identity built by rhetoric, politicians create their political marketing products then offered to the public so can be consumed as political support and choice.